Comparative Evaluation of the Efficacy and Safety of Brimonidine Generics in Glaucoma Therapy - A. A. Antonov; A. A. Vitkov; I. V. Kozlova; A. A. Komarov; E. D. Semenov (Oftalʹmologiâ, 2023)
Glaucoma is a chronic neurodegenerative disease that eventually leads to irreversible blindness. The main risk factor for the development and progression of glaucoma is elevated IOP. In cases where the use of prostaglandin analogues is limited, brimonidine is the most rational choice as initial therapy. It is the only molecule that both reduces aqueous humor production and enhances uveoscleral outflow. The use of several hypotensive drugs for a long time can lead to pronounced changes in the tissues of the anterior segment of the eye. In this case, there are complaints characteristic of the dry eye syndrome. The aggravation of this condition can affect the adherence of patients to treatment and worsen the course of the disease. Therefore, it is important to prescribe hypotensive drugs that have a sufficient hypotensive effect with a good safety profile. Purpose. To evaluate the efficacy and safety of Brimonidine SZ in combination therapy for glaucoma after changing the hypotensive regimen. Patients and methods. The study was conducted in a group of 50 patients (50 eyes) with initial or advanced drug-compensated primary open-angle glaucoma (mean age 64.8 years), among them there were 27 (54 %) women and 23 (46 %) men. In patients included in the study, brimonidine 0.15 % or 0.2 % was replaced with Brimonidine SZ as part of combination hypotensive therapy. To analyze the results obtained, data on corneal-compensated IOP, the degree of corneal staining with fluorescein, assessments of conjunctival hyperemia, indicators of the OSDI questionnaire and the level of adherence to treatment at the initial visit, as well as 1 and 3 months after changing the hypotensive regimen, were compared. Results. There were no statistically significant differences in the level of IOP at different times after changing the hypotensive regimen. Objective indicators of the state of the tissues of the anterior surface of the eye did not change. According to the results of the evaluation of the main signs of dry eye syndrome (OSDI) and the degree of adherence of patients to treatment, no significant changes were found either. Conclusion. Brimonidine SZ has a similar hypotensive efficacy with brimonidine 0.15 % and 0.2 % as part of combination hypotensive therapy. The safety profile of Brimonidine SZ is comparable to analogues, which allows us to consider this drug as a possible alternative when choosing hypotensive therapy.